تطور الخصائص التنظيمية للمقاولات المستدامة من خلال إدارة النمو - selmi, abdeldjabar (Finance and Business Economies Review, 2018)
Societies seek to achieve the development which is in harmony with environmental controls and social requirements, through the role of entrepreneurship in the development, so it has become necessary to integrate the social and environmental dimensions in the strategy of this entrepreneurship side by side the economic objectives, which contribute to the creation of sustainable entrepreneurship, to increase its ability in creating more value added in economy through its life longer. But this role can only be achieved if the entrepreneurship is able to survive and continue in a changing and turbulent environment, a lot of enterprises that have recently been founded during the first four years are exposed to death because they have new knowledge so they characterised by economic value with high incertitude, while the enterprises which were present in the market have previous and accumulate knowledge, consequently, its economic uncertainty is weak.